Bioactive Compounds from Halodule uninervis: Phytochemical Characterization and Antimicrobial Activity Against Clinical Pathogens - M. Kalaivani; S. Sivanantham; V. Geetha; S. Rohith; P. Sabarisan; G. Sachin; G. Sanjay; K. Roshini (International Journal of Science, Strategic Management and Technology, 2026)
Halodule uninervis is a tropical marine seagrass belonging to the family Cymodoceaceae and represents a potentially valuable source of structurally diverse marine bioactive compounds. The present study aimed to investigate the phytochemical composition and antimicrobial potential of H. uninervis collected from the Mandapam region of Ramanathapuram, Tamil Nadu, India. The collected seagrass biomass was thoroughly washed, dried, powdered, and subjected to aqueous extraction and Soxhlet extraction using ethanol and acetone. The resulting extracts were evaluated through qualitative phytochemical screening for phenols, tannins, flavonoids, glycosides, saponins, terpenoids, alkaloids, steroids, carbohydrates, and proteins. Chromatographic profiling was further performed using paper chromatography and thin-layer chromatography (TLC), while total phenolic content (TPC) and total flavonoid content (TFC) were determined to assess the major phenolic and flavonoid constituents. The antimicrobial activity of the extracts was evaluated against selected clinical bacterial pathogens. The extracts exhibited solvent-dependent variation in their phytochemical profiles and antimicrobial responses. Among the tested extracts, the ethanolic extract showed pronounced antibacterial activity against Pseudomonas aeruginosa and measurable activity against Salmonella typhi. The chromatographic and phytochemical findings further indicated the presence of diverse secondary metabolites that may contribute to the observed biological activity. Overall, the findings demonstrate the phytochemical diversity and preliminary antimicrobial potential of H. uninervis and support its consideration as a promising marine resource for the discovery of biologically active natural products. Further studies involving compound isolation, spectroscopic characterization, quantitative chemical profiling, minimum inhibitory concentration determination, and mechanistic evaluation are required to identify the constituents responsible for the observed antimicrobial activity and establish their potential biomedical applications.